2013
DOI: 10.1002/pdi.1748
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of liraglutide 1.2mg in patients with mild and moderate renal impairment: the ABCD nationwide liraglutide audit

Abstract: Liraglutide is not predominantly eliminated by renal excretion. We assessed its safety and efficacy among patients with mild and moderate renal impairment.Patients from a nationwide audit of liraglutide (1.2mg) use were divided according to pre-treatment renal function calculated by the Cockcroft-Gault formula. Adverse events, liraglutide discontinuation and changes in HbA1c, weight, systolic blood pressure and serum creatinine were compared between groups of different pre-treatment renal function.As compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…However, when adjusted for other variables including age, renal function became non-significantly associated with GISE outcomes. A pharmacokinetic study testing the 0.75 mg dose of liraglutide showed no increase in drug exposure in patients with renal impairment [17]. The Prescribing Information for liraglutide have reported that liraglutide is metabolised endogenously much like large proteins rather than having a specific organ as a major route of elimination, and with no significant elimination through the faeces or urine [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, when adjusted for other variables including age, renal function became non-significantly associated with GISE outcomes. A pharmacokinetic study testing the 0.75 mg dose of liraglutide showed no increase in drug exposure in patients with renal impairment [17]. The Prescribing Information for liraglutide have reported that liraglutide is metabolised endogenously much like large proteins rather than having a specific organ as a major route of elimination, and with no significant elimination through the faeces or urine [14].…”
Section: Discussionmentioning
confidence: 99%
“…ABCD also conducted an audit on the safety and efficacy of liraglutide 1.2 mg daily in 1791 patients with mild and moderate renal impairment and found that at 6 months there were significant reductions in HbA1c (−1.0 to −1.1%) and weight (−3.6 to −3.8 kg) which was not affected by degree of renal function . Minor hypoglycaemia was not more commonly reported in those with renal impairment and GI side effects were likely to occur at all stages of renal function although those with mild and moderate renal impairment were more likely to discontinue liraglutide (adjusted OR 2.32 [95% CI 1.45‐3.74] and 2.37 [95% CI 0.97‐5.81]), respectively.…”
Section: Hierarchy Of Evidencementioning
confidence: 99%
“…The Association of British Clinical Diabetologists (ABCD) conducted a nationwide audit in the UK to assess the safety and effectiveness of liraglutide in real-life clinical practice. Data from this audit demonstrated that, after 6 months of treatment, liraglutide 1.2 mg was effective in terms of reducing HbA 1c (more so in individuals with a higher baseline HbA 1c ) and well tolerated [ 9 , 10 ]. Furthermore, data from the IMS Health integrated claims database in the USA demonstrate that, in clinical practice, liraglutide (once daily) has greater effectiveness [in terms of HbA 1c reduction and improved glycemic goal attainment (HbA 1c <7.0%)] compared with either exenatide (GLP-1RA, twice daily) or sitagliptin [dipeptidyl peptidase-4 (DPP-4) inhibitor, once daily] in patients with T2D [ 11 ].…”
Section: Introductionmentioning
confidence: 99%